Pathological language-switching/mixing and its relationship to domain-general cognitive control - Fyndanis, Valantis; Lehtonen, Minna (My University, 2021)
This chapter constitutes a narrative review on the so-called pathological language mixing and switching, with primary focus on multilingual persons with aphasia. Domain-general cognitive control is assumed to be a central aspect of bilingual language use and is strongly involved in switching between languages. However, this assumed relationship has not received the empirical scrutiny it deserves. In this review, we ask whether and when language switching/mixing in brain-damaged participants should be considered a control deficit and when it can be better characterized as a communicative strategy of the participants. We present opposing views on the legitimacy of using the term pathological switching/mixing and propose a way of reconciling these views. We also ask to what extent possible language control deficits underlying so-called pathological switching/mixing overlap with domain-general cognitive control functions, as measured by tasks of executive functions, and look into the neural correlates of these functions. This question addresses the relationship between language control and domain-general cognitive control. It therefore also touches upon the underlying assumptions behind the idea that frequent language switching/mixing could train cognitive control functions, possibly leading to a bilingual advantage in cognitive abilities, a hotly debated topic.
Keywords: Bilingualism; Multilingualism; Language switching/mixing; Cognitive control